Isomerization and degradation of all-trans-β-carotene during in-vitro digestion - Wenyang Tao; Xingqian Ye; Yanping Cao (Food Science and Human Wellness)
To investigate the behavior of all-trans-β-carotene during digestion, in-vitro digestion coupled with HPLC-DAD, Raman spectroscopy and Fourier transform-infrared spectroscopy were used to monitor it. All-trans-β-carotene reduced by 75% during the in-vitro digestion and had a highest degradation during intestinal digestion compared with oral and gastro digestion. All-trans-β-carotene occurred isomerization and degradation during oral digestion and occurred degradation during gastro and intestinal digestion. Isomers were identified as 15-cis-β-carotene and 9-cis-β-carotene, degradation products were compounds with function group of C–O, C–O–C or C=C–C=C. The biological fate of β-carotene during digestion was clarified, and one of the reasons for low bioavailability of β-carotene was explained by high degradation rate during digestion.